Age of Onset and Dominance in the Choice of Subject Anaphoric Devices: Comparing Natives and Near-Natives of Two Null-Subject Languages - Di Domenico, Elisa; Baroncini, Ioli (Frontiers in Psychology, 2019)
Several studies have highlighted the role of cross-linguistic influence in determining the over-use of overt subject pronouns in near-native speakers of a null-subject language as Italian. In this work we inquire on the role of factors different from cross-linguistic influence in the choice of anaphoric devices in near-natives, such as age of onset of exposure and dominance. In order to do so, comparing the productions of two groups of natives speakers, we first single out two null-subject languages, Italian and Greek, which do not differ significantly as far as subject anaphoric devices are concerned and thus instantiate a suitable language combination to investigate the role of factors other than cross-linguistic influence in bilingual speakers of these two languages (Study 1). In Study 2, we compare the productions of a group of native speakers and two groups of near-native speakers in Italian: Greek-Italian bilinguals from birth and L2ers of Italian with Greek as an L1. Results reveal that over-use of overt pronouns in near-natives occurs in the absence of cross-linguistic influence and that age of onset of exposure is a relevant factor: while bilinguals from birth do not differ from native speakers, L2ers over-use overt pronouns compared to both native speakers and bilinguals from birth. In order to establish whether dominance is a possible factor determining bilinguals’ choice of subject anaphoric devices, in Study 3, we compare two groups of Greek-Italian bilinguals from birth: bilinguals living in Greece (whose predominant language is Greek) and bilinguals living in Italy (whose predominant language is Italian). Results reveal no effect of dominance in the production of overt subject pronouns. We found, however, an unexpected effect in the predominant language of one group: bilinguals living in Greece produce significantly more null pronouns and less lexical DPs in Greek compared to bilinguals living in Italy. We interpret this effect as stemming from the need to differentiate the two languages that these bilingual speakers have to handle in everyday life. Interestingly, this effect is found in the predominant language rather than in the non-predominant one.